In order to find the derivative of a exponential function, on its general form $a^x$ by the definition, I used limits.

$\begin{align*} \frac{d}{dx} a^x & = \lim_{h \to 0} \left [ \frac{a^{x+h}-a^x}{h} \right ]\\ \\ & =\lim_{h \to 0} \left [ \frac{a^x \cdot a^h-a^x}{h} \right ] \\ \\ &=\lim_{h \to 0} \left [ \frac{a^x \cdot (a^h-1)}{h} \right ] \\ \\ &=a^x \cdot \lim_{h \to 0} \left [\frac {a^h-1}{h} \right ] \end{align*}$

I know that this last limit is equal to $\ln(a)$ but how can I prove it by using basic Algebra and Exponential and Logarithms properties? Thanks

  • $\begingroup$ $a^h=\exp(\ln a \cdot h)$. Are you able to Taylor expand the exponential function? $\endgroup$ – anon Oct 30 '11 at 23:33
  • $\begingroup$ Well, can we use the definition but be a bit witty? Perhaps we could use the definition (along with the chain rule) on $\log y = \log (a^x)$? $\endgroup$ – davidlowryduda Oct 30 '11 at 23:43
  • $\begingroup$ I think it is worth mentioning that some authors (such as E. Landau) define the logarithm that way. $\endgroup$ – Pedro Tamaroff May 2 '12 at 21:23
  • $\begingroup$ I consider this to be a rather tricky issue. Let me explain. Let $a$ be positive real number. Then to \textit{define} $a^x$ algebraically is easy on the rationals, just ask that the standard exponent laws hold. But if you want to define $a^x$ for irrational values, you need to do some analysis. In particular you need to prove that $a^x$ is continuous on the rationals. $\endgroup$ – Baby Dragon Jun 3 '12 at 8:04
  • $\begingroup$ math.stackexchange.com/questions/1828962/… $\endgroup$ – user301988 Jul 4 '16 at 0:25

First, we prove it for $a=e$.

Let $\frac{1}{t} = e^h - 1$. Then $e^h = 1+\frac{1}{t}$, so $h = \ln(1 + \frac{1}{t})$. As $h\to 0$, we have $\frac{1}{t}\to 0$, so $t\to \infty$ (if $h\to 0^+$) or $t\to-\infty$ (if $h\to 0^-$). We have: $$\begin{align*} \lim_{h\to 0^+}\frac{e^h-1}{h} &= \lim_{t\to\infty}\left(\frac{1/t}{\ln(1+\frac{1}{t})}\right)\\ &= \lim_{t\to\infty}\frac{1}{t\ln(1+\frac{1}{t})}\\ &= \lim_{t\to\infty}\frac{1}{\ln\left( (1+\frac{1}{t})^t\right)}\\ &= \frac{1}{\ln\left(\lim_{t\to\infty}(1 + \frac{1}{t})^t\right)}\\ &= \frac{1}{\ln(e)}\\ &= 1. \end{align*}$$ Since we also have $$\begin{align*} \lim_{t\to-\infty}\left(1 + \frac{1}{t}\right)^t &= \lim_{n\to\infty}\left(1 - \frac{1}{n}\right)^{-n}\\ &= \lim_{n\to\infty}\frac{1}{(1 + \frac{-1}{n})^n}\\ &= \frac{1}{e^{-1}}\\ &= e,\end{align*}$$ a similar calculation shows that $$\lim_{h\to 0^-}\frac{e^h-1}{h} = 1.$$ Hence, $$\lim_{h\to 0}\frac{e^h-1}{h} = 1.$$

Now for arbitrary $a\gt 0$, $a\neq 1$, we rewrite $a^h = e^{h\ln(a)}$, and make the substitution $t = h\ln(a)$. Then the result follows from the case $a=h$ as Gerry Myerson shows.


It depends a bit on what you're prepared to accept as "basic algebra and exponential and logarithms properties". Look first at the case where $a$ is $e$. You need to know that $\lim_{h\to0}(e^h-1)/h)=1$. Are you willing to accept that as a "basic property"? If so, then $a^h=e^{h\log a}$ so $$(a^h-1)/h=(e^{h\log a}-1)/h={e^{h\log a}-1\over h\log a}\log a$$ so $$\lim_{h\to0}(a^h-1)/h=(\log a)\lim_{h\to0}{e^{h\log a}-1\over h\log a}=\log a$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.